2009 39th IEEE Frontiers in Education Conference 2009
DOI: 10.1109/fie.2009.5350571
|View full text |Cite
|
Sign up to set email alerts
|

On the development of a professional identity: engineering persisters vs engineering switchers

Abstract: Decline in engineering enrollment continues and renewed efforts are required to improve enrollment and diversity. Herein, we address this problem by conducting research to understand engineering students through the lens of identity theory. Implications of this effort are twofold: (1) to contribute to our basic understanding of engineering students' identities as well as what factors (experiences and settings) foster the formation and transformation of these identities during the undergraduate experience, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 17 publications
(24 reference statements)
3
168
0
Order By: Relevance
“…225-6, 232). This is not simply an issue of personality; organizational, institutional, and situational factors play a role in shaping identity (Olga Pierrakos et al, 2010).…”
Section: What Is Identity?mentioning
confidence: 99%
“…225-6, 232). This is not simply an issue of personality; organizational, institutional, and situational factors play a role in shaping identity (Olga Pierrakos et al, 2010).…”
Section: What Is Identity?mentioning
confidence: 99%
“…Perhaps this initial hesitation and uncertainty ends up causing a great number of college engineering students to question whether or not they want to pursue a career in engineering after graduation if they persist in the major that long; Lichtenstein et al reported that only 42% of college engineering seniors in their study definitely intended to pursue a career in engineering upon graduation 28 . Research seems to suggest that students who have a limited knowledge of the profession and limited experience with engineering like activities before college are more likely to switch out of the major 26 . This evidence seems to reinforce the idea that every individual student has a different view / understanding of engineering identity; due to their various backgrounds, pressures, motivations, and expectations of engineering, individuals likely shape their own definitions of what an engineer is as well as how they fit that image.…”
Section: General Uncertainty and Hesitation Toward Engineeringmentioning
confidence: 99%
“…To me, what stands out as particularly striking is the superiority that Kimmy attributes to engineering majors. Kimmy's response seems to highlight how individuals that categorize themselves as part of a group, in this case engineers, leads them to display in-group favoritism when comparing themselves to other groups 26 . I believe that these sorts of beliefs are likely very influential in the formation for student identity development and navigation.…”
Section: Internal Pressuresmentioning
confidence: 99%
See 2 more Smart Citations